2018
DOI: 10.1002/ejlt.201700039
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule in Ruminant: Major and Minor Compounds, Nutritional Regulation and Differences Among Species

Abstract: Recent knowledge is presented on the composition of ruminant milk fat fractions and the nutritional strategies known to alter their amount. The development of lipidomic and proteomic analyses has allowed for the characterization of minor components, such as proteins, liposoluble vitamins, and phospholipids of the milk fat globule (MFG), in addition to the triacylglycerols (TAG), which are the major constituents of the MFG core. Few differences in these components among ruminant species exist, and they have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 276 publications
(349 reference statements)
3
83
0
Order By: Relevance
“…This phenomenon could explain the limited transfer of C18: 3n -3 into milk fat because C18: 3n -3 is present highly in phospholipids (Bernard et al, 2008;Stamey Lanier et al, 2013). Moreover, a possible regulation of the glycerol transferase enzymes involved in the triglyceride synthesis (glycerol-3-phosphate acyltransferase, acylglycerol phosphate acyltransferase, and diacylglycerol O-acyltransferase) by C18: 2n -6 or C18: 3n -3 availability could be implicated and interact with the transfer of these FA into milk (Bernard et al, 2008(Bernard et al, , 2018.…”
Section: Milk Total C18 Fatty Acids Cis and Trans Isomersmentioning
confidence: 99%
“…This phenomenon could explain the limited transfer of C18: 3n -3 into milk fat because C18: 3n -3 is present highly in phospholipids (Bernard et al, 2008;Stamey Lanier et al, 2013). Moreover, a possible regulation of the glycerol transferase enzymes involved in the triglyceride synthesis (glycerol-3-phosphate acyltransferase, acylglycerol phosphate acyltransferase, and diacylglycerol O-acyltransferase) by C18: 2n -6 or C18: 3n -3 availability could be implicated and interact with the transfer of these FA into milk (Bernard et al, 2008(Bernard et al, , 2018.…”
Section: Milk Total C18 Fatty Acids Cis and Trans Isomersmentioning
confidence: 99%
“…One possible reason for this is that FA proportions in the rumen fluid do not fully reflect those in the duodenum, which is the main absorption site for FA (Szczechowiak et al, 2016). The milk FA proportions also depend on the activity of mammary gland desaturases, especially ∆ 9 desaturase, and genes participating in milk fat synthesis and secretion (Brzozowska and Oprządek, 2016;Bernard et al, 2018;Cappucci et al, 2018).…”
Section: Itemmentioning
confidence: 99%
“…Analyzed using LSD method of LS-means with the PDIFF option. 1 The dietary treatment (D) species (S) and the interaction between dietary treatment  species (D  S) effects were analyzed by ANOVA using the mixed procedure of SAS (SAS, Inc. 9.4) with animal in group as random effect. 2 SEM are means of error types obtained for each Latin square (species) by ANOVA analysis.…”
Section: Composition In Fa Of the Tg And Ffa Plasma Fractionsmentioning
confidence: 99%
“…In the literature, a great number of studies reported large effects of diets, particularly lipid supplementation, on ruminant milk fatty acid (FA) composition . These lipid supplements were studied for their capacity to increase the poly‐unsaturated fatty acid (PUFA) content in milk, particularly omega 3 FA or conjugated linoleic acid (CLA), which are known for their beneficial effects on human health .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation